CHARACTERISTICS OF EATING BEHAVIOR IN DAYCARE TREATMENT SCHIZOPHRENIA PATIENTS (Vietnam Journal of Community Medicine, 2024)
Schizophrenia is a severe, progressive psychotic disorder with diverse clinical manifestations. In thetreatment procedure, besides taking medicine regularly, diet and nutrition also play an important role.The problems related to eating behaviors among schizophrenia patients can be caused by positivesymptoms (delusions of being poisoned, hallucinations...) or negative symptoms (dullness, lack ofpurposes). Each schizophrenia patient may have different eating/nutrition problems. Therefore, it isextremely necessary to pay attention to the eating behaviors of schizophrenia patients in both theacute and maintenance treatment phases. Objective: The study aims to describe the characteristicsof eating behavior among schizophrenia patients receiving daycare treatment at Mai HuongDaycare Psychiatric Hospital, 2022. Subjects and research methods: A descriptive study on 108schizophrenia patients receiving daycare treatment at Mai Huong Daycare Hospital from February2022 to October 2022. Results: Eating behaviors such as anorexia, changes in appetite, and lessdrinking were common symptoms in the study group, with the same results in both men and women.The prevalence of anorexia symptoms in the study group is 51.9%. The sex difference in anorexiagroup is statistically significant with p-value = 0.04. The rate of changes in taste in the study groupwas 66.7%. Symptoms of resistance to eating were found in 5 acute-symptom cases. This differencewas statistically significant with 99% confidence (p = 0.00). In the study, there were no binge eatingpatients as well as dirty eating patients. The percentage of patients who rarely drinks in the studygroup was 63.9%.
Keywords: Eating behavior, schizophrenia, daycare inpatients, psychiatric patients.